2002
DOI: 10.1021/jf020162+
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing Techniques at Industrial Scale on Orange Juice Antioxidant and Beneficial Health Compounds

Abstract: Phenolic compounds, vitamin C (L-ascorbic acid and L-dehydroascorbic acid), and antioxidant capacity were evaluated in orange juices manufactured by different techniques. Five processes at industrial scale (squeezing, mild pasteurization, standard pasteurization, concentration, and freezing) used in commercial orange juice manufacturing were studied. In addition, domestic squeezing (a hand processing technique) was compared with commercial squeezing (an industrial FMC single-strength extraction) to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
119
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(138 citation statements)
references
References 32 publications
17
119
1
1
Order By: Relevance
“…Besides, the sample of home-made OJ was built to reflect the usual attitudes and practices of French consumers, as recorded from a consumer survey. These characteristics made our work original as compared with previous studies in this area, which did not consider commercially available OJ or home-made OJ prepared following usual consumer's practices (e.g., [6] [17] [22]). …”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Besides, the sample of home-made OJ was built to reflect the usual attitudes and practices of French consumers, as recorded from a consumer survey. These characteristics made our work original as compared with previous studies in this area, which did not consider commercially available OJ or home-made OJ prepared following usual consumer's practices (e.g., [6] [17] [22]). …”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Ferreira et al (2002) found that total phenolic content in pears decreased by 64% under sun-drying conditions. Freezing, pasteurization, boiling and microwave cooking can reduce the total antioxidant levels (Gil-Izquierdo et al 2002;Guyot et al 2003;Aziz et al 1998). One exception is perhaps the processing of tomatoes.…”
Section: Maturity Postharvest Storage and Processingmentioning
confidence: 99%
“…Besides phenolic compounds, Vitamin C is considered the most important water-soluble antioxidant that contributes to the antioxidant cellular defence against oxidative stress. The profile of the antioxidant compounds in OJ shows quantitative and qualitative differences related to the genotype (variety), environmental conditions (sunlight, rain, temperature), agronomic practices (type of crop and harvesting conditions), fruit maturity and technological processes (thermal, mechanical) and storage (Klimczak et al, 2007), all of which affect compound content and consequently antioxidant capacity (Dhuique-Mayer et al, 2005;Gil-Izquierdo et al, 2002;Mouly et al, 1997).…”
Section: Introductionmentioning
confidence: 99%